The actual cost price in sale of murabahah - Tahir, Ibrahim Nuhu (International Association of Computer Science and Information Technology Press (IACSIT), 2016)
This paper critically analyses business transactions that involve product costing methods that have been controversial in the past and have continued to be so in the present. This is highly attributable to the advancement of modern technology which has brought about new activities and responsibilities which emerge on a daily basis. The controversy is regarding a sale that is known to economists and the Muslim jurists as the sale of Murabahah. The analysis in this paper addresses solely the most important pillar in this type of contract which is what is currently known as the cost price in which the mark-up or profit will be based on. The scholars categorized what can or cannot be considered as the cost into three categories; A category where the jurists all agree with it to be included in the cost, category where they all agree with it to be excluded, and a category where controversy lies [1]. The analysis in this paper addresses and deals with the last category where controversy exists. In this paper the differing opinions are critically analyzed through reliance on the primary sources as well as a sound logical reasoning. The paper concludes with a clear stand towards those doubtful affairs in relation to the cost price of the item to be sold on Murabahah basis. Similarly it is part of the responsibility of this paper to make some recommendations for the Islamic Banks on how to utilize and make a proper use of these types of businesses for the success of the Islamic banking system in the future.